QUANTUM FLUX REDISTRIBUTION DURING MOLECULAR PHOTODISSOCIATION - Manolopoulos, D; Alexander, M (1992)
A new method proposed recently by Alexander for studying the mechanisms of inelastic collisions is adapted to the study of molecular photodissociation. This adaptation involves the determination of the current density associated with a driven photodissociation wave function at each fixed scattering energy, and yields a picture of how, as a function of the dissociation coordinate, the outgoing photofragment flux rises in the Franck-Condon region on absorption of the photon and how it redistributes between the available internal channels as the photofragments move apart. This picture complements the usual time-dependent picture of photodissociation, allowing one in particular to analyze the mechanism of the photodissociation in detail at each individual excitation laser frequency. A study of flux redistribution in a simple two-state model for the electronically nonadiabatic photodissociation of methyl iodide is presented as a first illustration of the approach. © 1992 American Institute of Physics.